Acquisition of educational values at the Real Madrid Foundation’s social-sports schools - Ortega-Vila, Gema; Ortega-Toro, Enrique; Giménez-Fuentes-Guerra, Francisco Javier; Robles-Rodríguez, José; Alarcón-López, Francisco; Abad-Robles, Manuel Tomás (Frontiers in Psychology, 2024)
The objective of this study was to analyse the impact of the educational programme of the Real Madrid Foundation (RMF) on the acquisition of educational values at social-sports football and basketball schools among children aged between 12 and 16 years in Italy, Romania, Spain and the United Kingdom. The most significant results showed that: a) between the 20-21 and 21-22 seasons, there were statistically significant increases in personal and team success, self-fulfilment, personal and group superiority, health and physical fitness, and peaceful behaviour; b) the increase in variables being studied was different according to the country analysed in such a way that: in the personal and team success dimension there was a rise in the United Kingdom and Italy; in self-fulfilment there was an increase in the United Kingdom; in the personal and group superiority dimension there was a rise in Italy and Romania; in the health and physical fitness dimension there was an increase in social-sports schools in the United Kingdom and Italy; in the peaceful be-haviour dimension there was a rise in social-sports schools in the United Kingdom and a drop in social-sports schools in Romania. There were very significant improvements in the majority of dimensions and countries, although the development of the various dimensions is different and specific to every one of the distinct countries, meaning that it is necessary to keep adapting the educational programme of the Real Madrid Foundation in line with the sociocultural characteristics of each of the countries in which it is implemented.